THE ROLE OF EXISTENTIAL-HUMANISTIC COUNSELING TECHNIQUES IN OVERCOMING BURNOUT AMONG STUDENTS IN HIGHER EDUCATION - Achmad Navis Afkari; Mudafiatun Isriyah; Dewi Masyitoh (EDUCATIONE, 2025)
Academic burnout among final-year university students is a critical issue, particularly for those balancing thesis completion with part-time employment and personal challenges. This study explores the role of existential-humanistic counseling in alleviating academic burnout experienced by students in the Guidance and Counseling Program at Universitas PGRI Argopuro Jember. Using a qualitative case study approach, data were collected through semi-structured interviews, observation, and documentation involving ten final-year students showing symptoms of burnout. Thematic analysis revealed three key themes: awareness of burnout, the impact of burnout on mental and academic well-being, and coping strategies. Findings showed that students experienced emotional exhaustion, motivation decline, and behavioral changes such as procrastination and social withdrawal. Coping mechanisms ranged from mindfulness and cognitive reframing to social engagement and creative activities. Existential-humanistic counseling was found to support students by fostering self-awareness, emotional resilience, and personal meaning, offering a deeper and culturally relevant alternative to conventional behavioral models. The study underscores the need for integrative counseling practices that address existential dimensions of student crises. It contributes to educational psychology and counseling practice by demonstrating how personal responsibility and meaning-making can transform burnout into an opportunity for growth. Future research should include diverse academic contexts and incorporate mixed-method designs to enhance generalizability and rigor.